Analysis of realm of valor and its business model on pc and mobile platform comparison - Punyawee Anunpattana,; Mohd Nor Akmal Khalid,; Iida, Hiroyuki; Umi Kalsom Yusof, (Penerbit Universiti Kebangsaan Malaysia, 2018)
This paper explores the attractiveness and sophistication of Realm of Valor (ROV) using game refinement theory and analyzes its business model by gamification. ROV is one of the most attractive and popular MOBA games in mobile platform. It is free-to-play (F2P) game which is the most popular business model for mobile platform. The result shows that ROV has game refinement value in sophisticated zone that implies entertainment and competitiveness experiences. Moreover, the results are used to make a comparison of platform transformation of MOBA genre which causes from quick time battle characteristics. We also present the result of evolution skin revenue essentially increase over the year due to number of mobile users. Finally, ROV is one of the best examples in monetization while introducing suitable characteristics for the mobile platform such that players can feel entertainment and excitement.